Outcome of PCNL by Supracostal Approach for Staghorn Stone in Comparison with Infracostal Approach - Hasan, Md Mahmud; Rahman, Md Mostafizur; Hossain, Momtaz; Kabir, Md Golam; Rashid, Muhammad Mamunur; Arafuzzaman, Khondoker; Islam, Merajul; Ahmed, Masud; Alam, Md Mahmudul (Bangladesh Journal of Urology, 2022)
Introduction: Percutaneous nephrolithotomy (PCNL) is the treatment of choice for staghorn stones, large renal stones and some upper ureteric stones. The subcostal approach in staghorn stones has the problem of angulation and torque on the kidney but a supracostal approach provides direct access and thereby facilitates better stone clearance. The purpose of this study was to compare stone clearance rate and also to observe the complications between supracostal and infracostal access routes in managing staghorn calculi. Materials and Methods: The present quasi-experimental study was conducted in the Department of Urology, of the three hospitals in Dhaka. A total of 68 subjects (32 in Supracostal group and 36 in Infracostal group) with staghorn stone who were treated by PCNL were the study subjects. Data were collected by interview of the patients, clinical examination and laboratory investigations using the research instrument. Data were processed and analysed using software SPSS version 11.5. The outcome measures were stone clearance, success rate, duration of hospital stay and complications encountered by the patients of either group. Results: The findings of the study showed that there was no significant difference between the groups in terms of age, sex and body mass index. The groups were also similar in terms of side of kidney involved and incidence of multiple stones. As outcome was considered, stone-free and success rate, it was higher in the supracostal group compared to that in the infracostal group, while the rate of complications was higher in the infracostal group than that in the supracostal group. Some patients in both the groups required additional maneuver to augment stone clearance but not statistically significant. The additional maneuvers were extracorporeal shock wave lithotripsy (ESWL) ,ureteroscopy with intracorporeal lithotripsy and PCNL. Conclusions: The study concludes that outcome of percutaneous nephrolithotomy for staghorn stone clearance is better in supracostal than infracostal approach and the rate of complications was higher in infracostal approach with higher duration of hospital stay. Bangladesh J. Urol. 2021; 24(2): 193-199